Method for adsorbing and separating cycloalkanes and dimethyl alkanes in C5 / C6 alkanes
By using Cs+ and/or Rb+ ion exchanged FAU-type molecular sieve adsorbents and liquid-phase simulation mobile bed process, the problem of low separation efficiency of cycloalkanes and dimethylalkanes in C5/C6 light hydrocarbon fractions is solved, and the separation of high-purity components and efficient utilization of resources is achieved.
Patent Information
- Application Number
- CN202311332991.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively separate cycloalkanes and dimethylalkanes in C5/C6 light hydrocarbon fractions, resulting in low resource utilization efficiency.
The FAU-type molecular sieve containing Cs+ and/or Rb+ ion exchange is used as the adsorption agent, and the adsorption and separation is performed through the liquid phase simulation mobile bed process. Its selective adsorption of cycloalkanes and dimethyl alkanes is used, and combined with the use of desorption agent, the efficient separation of C5/C6 alkanes is achieved.
The separation of high-purity cycloalkanes and dimethyl alkanes has been achieved. As high-octane gasoline blending components, high-purity n-alkanes and monomethyl alkanes can be used as high-quality ethylene cracking raw materials, improving the utilization efficiency of resources.
Smart Images

Figure CN119822915A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of adsorption separation, and in particular to a method for adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes. Background Art
[0002] A large amount of C5 / C6 light hydrocarbon fractions are produced during crude oil processing, including reforming top oil, reforming pentane oil, hydrocracking light naphtha, etc. These fractions are basically sulfur-free, with low olefin and aromatic content, and can be used as environmentally friendly chemical and oil raw materials. Among these C5 / C6 light hydrocarbon fractions, isopentane has a high octane number, RON (research octane number) is 93; dimethyl paraffins include 2,2-dimethylbutane and 2,3-dimethylbutane, both of which have high octane numbers, RON 92 and 104 respectively; normal paraffins include n-pentane and n-hexane, both of which have low octane numbers, RON 62 and 25 respectively; monomethyl paraffins, except for isopentane, have a high octane number, while 2-methylpentane and 3-methylpentane have low octane numbers, RON 73 and 75 respectively; cyclopentane, methylcyclopentane and cyclohexane have high octane numbers, RON 85, 80 and 77 respectively. Therefore, isopentane, dimethyl paraffins and cycloalkanes with higher octane numbers in the C5 / C6 light hydrocarbon fraction are more suitable as gasoline blending components, while normal paraffins and 6-carbon monomethyl paraffins are not suitable for blending gasoline due to their low octane numbers. In the C5 / C6 light hydrocarbon fraction, except for isopentane with a lower boiling point, which can be directly separated by distillation, other hydrocarbon components have similar boiling points. For example, the boiling point difference between 2,3-dimethylbutane and 2-methylpentane is only 2.3°C. If they are to be separated by distillation, not only will the operating energy consumption of the device be very high, but multiple distillations will be required to separate the components rather than a single hydrocarbon. Therefore, if there is a suitable method to separate the remaining C5 / C6 components into two parts, one part is normal alkanes and monomethyl alkanes (excluding 2-methylpentane), which can be used as high-quality ethylene cracking raw materials or as C5 / C6 isomerization feed; the other part is dimethyl paraffins and cycloalkanes, which can be used as high-octane gasoline blending components, thus achieving more efficient utilization of C5 / C6 light hydrocarbon resources.
[0003] The adsorption separation method utilizes the selective adsorption effect of the adsorbent to separate different types of molecules. For example, the selective adsorption of normal alkanes by 5A molecular sieve can separate normal alkanes from C5 / C6 light hydrocarbons.
[0004] USP4595490 uses a gas phase isobaric adsorption separation method to separate light naphtha fractions. This method adsorbs normal alkanes in the C5 / C6 fraction on a 5A molecular sieve under gas phase conditions. After adsorption equilibrium, hydrogen is used as a displacement agent to remove the normal alkanes on the molecular sieve, thereby achieving separation of normal alkanes from other components.
[0005] USP5026951 discloses a method for separating normal alkanes in C5 / C6 fractions under liquid phase conditions using 5A molecular sieve as an adsorbent and n-butane as a desorbent. This method circulates the normal C5 / C6 alkanes in the extracted liquid and the desorbent n-butane back to the isomerization reactor, and the raffinate can also be sent to a deisohexanizer to separate the methylpentane therein as an isomerization raw material.
[0006] CN102452885B discloses an adsorption separation method for C5 / C6 isomerization products, which uses gas phase adsorption of n-pentane, n-hexane and monomethylpentane to obtain a residual oil as a high-octane blending component. 10 The normal alkanes are used as desorbents.
[0007] However, the above method can only separate normal alkanes from C5 / C6 light hydrocarbon feedstocks, and most of the monomethyl paraffins cannot be effectively separated. Summary of the invention
[0008] The purpose of the present disclosure is to provide a method for separating cycloalkanes and dimethylalkanes from C5 / C6 alkanes by adsorptive separation, which can separate C5 / C6 alkanes to obtain high-purity dimethylalkanes and cycloalkanes, as well as high-purity normal alkanes and monomethylalkanes.
[0009] In order to achieve the above object, the present disclosure provides a method for adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes, the method comprising the following steps:
[0010] S1, bringing the raw material to be separated into first contact with the adsorbent to obtain a material to be desorbed comprising cycloalkanes having a carbon number of 5-6, dimethylalkanes having a carbon number of 5-6 and the adsorbent, and a raffinate comprising normal alkanes having a carbon number of 5-6, monomethylalkanes having a carbon number of 5-6 and the desorbent;
[0011] S2, bringing the desorbent into second contact with the material to be desorbed to obtain an extract containing cycloalkanes having a carbon number of 5-6, dimethylalkanes having a carbon number of 5-6 and the desorbent;
[0012] The raw materials to be separated include normal alkanes with carbon atoms of 5-6, cycloalkanes with carbon atoms of 5-6, dimethylalkanes with carbon atoms of 5-6, and monomethylalkanes with carbon atoms of 5-6;
[0013] The adsorbent includes a FAU type molecular sieve, and the metal cations in the FAU type molecular sieve include Cs + ions and / or Rb + ion.
[0014] Optionally, in the FAU type molecular sieve, the Cs + ions and the Rb + The total degree of ion exchange is 20-70%;
[0015] Optionally, the silicon to aluminum ratio of the FAU type molecular sieve is 2.0-6.0;
[0016] Optionally, the FAU type molecular sieve includes an X type molecular sieve and / or a Y type molecular sieve.
[0017] Optionally, the water content of the adsorbent is less than 5 wt %.
[0018] Optionally, the boiling point difference between the desorbent and the raw material to be separated is more than 10°C;
[0019] Preferably, the desorbent includes one or more of normal alkanes with carbon atoms of 8-12, isoalkanes with carbon atoms of 8-12, and cycloalkanes with carbon atoms of 8-12.
[0020] Optionally, the temperature of the first contact and the second contact are 50-200° C., and the pressure are 1.0-4.0 MPa, respectively.
[0021] Optionally, a liquid phase simulated moving bed process is used to adsorb and separate cycloalkanes and dimethylalkanes from C5 / C6 alkanes, and the simulated moving bed comprises 8-24 adsorbent beds;
[0022] Step S1 comprises: bringing the raw material to be separated into the first contact with the adsorbent bed to obtain a raffinate containing the normal alkanes having a carbon number of 5-6, the monomethyl paraffins having a carbon number of 5-6 and a desorbent, and the adsorbent bed adsorbing the cycloalkanes having a carbon number of 5-6 and the dimethyl paraffins having a carbon number of 5-6 as the material to be desorbed;
[0023] Step S2 includes: bringing the desorbent into contact with the material to be desorbed for the second time to obtain the extract.
[0024] Optionally, the method further comprises:
[0025] Separating the extracted liquid to obtain the cycloalkanes with a carbon number of 5 to 6, the dimethylalkanes with a carbon number of 5 to 6 and the desorbent;
[0026] The raffinate is separated to obtain the normal alkanes with a carbon number of 5-6, the monomethyl alkanes with a carbon number of 5-6 and the desorbent.
[0027] Optionally, the method for preparing the adsorbent comprises the following steps:
[0028] (1) mixing a molecular sieve raw material, a binder and an auxiliary agent and performing a molding process to obtain a first product;
[0029] (2) heat treating the first product to obtain a second product;
[0030] (3) contacting a solution containing a metal source with the second product to perform an ion exchange reaction to obtain a third product;
[0031] (4) activating the third product;
[0032] The metal source includes a rubidium source and / or a cesium source;
[0033] The molecular sieve raw material includes NaY molecular sieve raw powder and / or NaX molecular sieve raw powder.
[0034] Optionally, in step (1), the binder includes one or more of a clay binder, silica sol and alumina sol;
[0035] The clay binder includes one or more of kaolin, halloysite and attapulgite;
[0036] The auxiliary agent includes one or more of lignin, sesbania powder, corn starch, bayberry tannin and methyl cellulose;
[0037] Optionally, the silicon-aluminum ratio of the NaX molecular sieve raw powder is 2.0-3.0, and the silicon-aluminum ratio of the NaY molecular sieve raw powder is 3.0-6.0.
[0038] Optionally, in step (1), on a dry basis, the weight ratio of the molecular sieve raw material to the binder is (80-95):(5-20);
[0039] On a dry basis, the amount of the auxiliary agent used is 1-5% by weight relative to the total weight of the molecular sieve raw material and the binder.
[0040] Optionally, step (1) further comprises: forming the product of the molding process into particles with a particle size of 0.30-1.00 mm, and performing a first drying process on the particles to obtain the first product;
[0041] Alternatively, the product of the molding process is subjected to the first drying process, and then formed into particles with a particle size of 0.30-1.00 mm to obtain the first product;
[0042] The conditions of the first drying treatment include: temperature of 80-200° C. and time of 1-4 hours.
[0043] Optionally, in step (2), the heat treatment conditions include: temperature of 500-700° C., time of 1-4 h;
[0044] Optionally, step (2) further comprises: contacting the solid product obtained by the heat treatment with a solution comprising an alkali source, an optional silicon source and an optional aluminum source, and subjecting the obtained mixture to optional aging treatment and crystallization treatment to obtain the second product;
[0045] In the mixture, the molar ratio of sodium element calculated as Na2O to silicon element calculated as SiO2 is (0.6-6.7):1, the molar ratio of silicon element calculated as SiO2 to aluminum element calculated as Al2O3 is (3.0-10.8):1; the molar ratio of H2O to sodium element calculated as Na2O is (55-220):1;
[0046] Optionally, the aging treatment conditions include: time of 1-24h, temperature of 30-60°C;
[0047] Optionally, the conditions of the crystallization treatment include: time of 1-12h, temperature of 80-98°C;
[0048] The alkali source includes sodium hydroxide and / or potassium hydroxide;
[0049] The silicon source includes sodium silicate and / or silica sol;
[0050] The aluminum source includes sodium metaaluminate and / or aluminum sol.
[0051] Optionally, in step (3), the cesium source includes one or more of cesium chloride, cesium nitrate and cesium sulfate;
[0052] The rubidium source includes one or more of rubidium chloride, rubidium nitrate and rubidium sulfate;
[0053] In the solution, the concentration of the metal source is 0.1-2.0 mol / L;
[0054] The conditions of the ion exchange reaction include: time of 1-3h, temperature of 20-99°C;
[0055] Optionally, step (3) further comprises: subjecting the solid product obtained by the ion exchange reaction to a second drying treatment to obtain the third product;
[0056] The conditions of the second drying treatment include: time of 1-4 hours and temperature of 80-200°C.
[0057] Optionally, in step (4), the temperature of the activation treatment is 200-500° C., and the time of the activation treatment is 1-4 h.
[0058] Through the above technical solution, the present application uses a method including Cs + ions and / or Rb+ The adsorbent of FAU molecular sieve with ion exchange can effectively adsorb and separate cycloalkanes and dimethylalkanes in C5 / C6 alkanes to obtain high-purity cycloalkanes and dimethylalkanes, which can be used as high-octane gasoline blending components. It can also obtain high-purity monomethylalkanes and normal alkanes, which can be used as high-quality ethylene cracking raw materials and as isomerization raw materials to produce light high-octane gasoline.
[0059] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0061] Figure 1 It is a schematic flow diagram of the method for adsorptive separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes disclosed in the present invention.
[0062] Figure 2 It is a schematic diagram of a process for separating cycloalkanes and dimethylalkanes from C5 / C6 alkanes by adsorption using a liquid phase simulated moving bed process according to an embodiment of the present disclosure.
[0063] Description of Reference Numerals
[0064] 1 pipeline for raw materials to be separated 7 pipeline for desorbent
[0065] 2 Desorbent pipeline 8 Desorbent pipeline
[0066] 3 Raffinate pipeline 100 adsorption tower
[0067] 4 Extraction liquid pipeline 200 Residual liquid tower
[0068] 5N-alkanes and monomethyl paraffins pipeline 300 extraction liquid tower
[0069] 6 Cycloalkane and dimethylparaffin pipeline 11-22 adsorption column DETAILED DESCRIPTION
[0070] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0071] The present disclosure provides a method for separating cycloalkanes and dimethylalkanes from C5 / C6 alkanes by adsorption, the method comprising the following steps:
[0072] S1, bringing the raw material to be separated into first contact with the adsorbent to obtain a material to be desorbed comprising cycloalkanes having a carbon number of 5-6, dimethylalkanes having a carbon number of 5-6 and the adsorbent, and a raffinate comprising normal alkanes having a carbon number of 5-6, monomethylalkanes having a carbon number of 5-6 and the desorbent;
[0073] S2, bringing the desorbent into second contact with the material to be desorbed to obtain an extract containing cycloalkanes having a carbon number of 5-6, dimethylalkanes having a carbon number of 5-6 and the desorbent;
[0074] The raw materials to be separated include normal alkanes with carbon atoms of 5-6, cycloalkanes with carbon atoms of 5-6, dimethylalkanes with carbon atoms of 5-6, and monomethylalkanes with carbon atoms of 5-6;
[0075] The adsorbent includes a FAU type molecular sieve, and the metal cations in the FAU type molecular sieve include Cs + ions and / or Rb + ion.
[0076] In the present disclosure, in step S1, the desorbent in the raffinate does not originate from the first contact, but from the upstream of the simulated moving bed, and may also originate from the desorbent in the downstream adsorbent bed.
[0077] In the present disclosure, the normal alkanes with carbon number of 5-6 may include, for example, normal pentane and / or normal hexane; the cycloalkanes with carbon number of 5-6 may include, for example, one or more of cyclohexane, cyclopentane, and methylcyclopentane; the dimethyl paraffins with carbon number of 5-6 may include, for example, 2,2-dimethylbutane and / or 2,3-dimethylbutane; the monomethyl paraffins with carbon number of 5-6 may include, for example, one or more of 2-methylpentane, 3-methylpentane, and isopentane. There is no specific restriction on the ratio of the types of alkanes. For example, when the normal alkanes with a carbon number of 5-6 include n-pentane and n-hexane, there is no specific restriction on the ratio between the two. The present disclosure also does not impose any specific restriction on the ratio of the normal alkanes with a carbon number of 5-6, the cycloalkanes with a carbon number of 5-6, the dimethylalkanes with a carbon number of 5-6 and the monomethylalkanes with a carbon number of 5-6 in the adsorbed raw material, that is, the method disclosed in the present disclosure can adsorb and separate any content of cycloalkanes and dimethylalkanes in C5 / C6 alkanes.
[0078] The present disclosure unexpectedly discovered that Cs + ions and / or Rb +The ionic FAU molecular sieve has a strong adsorption selectivity for dimethyl paraffins and cycloalkanes, but a weak adsorption for normal paraffins and monomethyl paraffins. Therefore, the C5 / C6 alkane containing normal paraffins with carbon atoms of 5-6, cycloalkanes with carbon atoms of 5-6, dimethyl paraffins with carbon atoms of 5-6, and monomethyl paraffins with carbon atoms of 5-6 can be separated into the above two parts by adsorption, so that normal paraffins and monomethyl paraffins can be used as high-quality ethylene cracking raw materials or as C5 / C6 isomerization reaction feedstocks; dimethyl paraffins and cycloalkanes can be used as high-octane gasoline blending components, thereby achieving more efficient utilization of resources. Since the FAU molecular sieve has a stronger adsorption selectivity for aromatics, the C5 / C6 alkane raw material to be separated does not contain aromatics, that is, the aromatic content therein is less than 0.1% by weight, which requires the components with a boiling point higher than benzene (80.1°C) to be cut off when the fraction is cut. The raw materials to be separated according to the present disclosure are reformed tops and / or hydrocracking light naphtha, which are basically free of olefins and may be free of aromatics after appropriate cutting. For raw materials containing more olefins, olefins can be converted into alkanes by hydrotreatment. If there are more aromatics in the raw materials, the aromatics can also be separated out by aromatic extraction or adsorption separation. The 2-methylpentane separated by the method disclosed in the present disclosure has a higher octane number, so it can also be separated from the normal pentane, normal hexane and monomethyl paraffins with 6 carbon numbers by distillation, and the 2-methylpentane obtained after separation is used to blend gasoline.
[0079] In the present disclosure, the cations in the molecular sieve also include Na + ion.
[0080] According to one embodiment of the present disclosure, in the FAU type molecular sieve, the Cs + ions and the Rb + The total exchange degree of ions is 20-70%, preferably 40-70%; the above exchange degree indicates that Cs + Ions and Rb + The percentage of exchangeable cation sites in the molecular sieve occupied by ions. The specific measurement methods include: using X-ray fluorescence spectroscopy (XRF) to analyze the mass fractions of Na2O, Cs2O, and Rb2O in the adsorbent, recorded as m N 、m C and m R , then Cs + Degree of ion exchange = m C / M C / (m C / M C +m N / M N +m R / M R ), Rb +Degree of ion exchange = m R / M R / (m C / M C +m N / M N +m R / M R ), Cs + Ions and Rb + Total ion exchange degree = Cs + Ion exchange degree + Rb + The degree of ion exchange. N 、M C and M R are the molar masses of Na2O, Cs2O and Rb2O respectively.
[0081] According to one embodiment of the present disclosure, the silicon-aluminum ratio of the FAU type molecular sieve is 2.0-6.0. In the present disclosure, the silicon-aluminum ratio refers to the molar ratio of silicon dioxide to aluminum oxide.
[0082] According to one embodiment of the present disclosure, the FAU type molecular sieve includes X type molecular sieve and / or Y type molecular sieve. When the FAU type molecular sieve includes both X type molecular sieve and Y type molecular sieve, there is no specific restriction on the ratio between the two, that is, any ratio can realize the technical solution of the present disclosure.
[0083] In the present disclosure, pH values are all measured values under the conditions of 25° C. and standard atmospheric pressure.
[0084] According to one embodiment of the present disclosure, the water content of the adsorbent is less than 5 weight %, wherein "the water content of the adsorbent" refers to the content of water relative to the total weight of the adsorbent; when the water content of the adsorbent is within the range of the present disclosure, higher adsorption selectivity and effective adsorption capacity of cycloalkanes and dimethylalkanes can be obtained.
[0085] According to one embodiment of the present disclosure, the boiling point difference between the desorbent and the raw material to be separated is more than 10°C. The desorbent and the raw material to be separated have a large boiling point difference, which is convenient for distillation separation from the components in the extract and the residual liquid to obtain the separated product and realize the recycling of the desorbent, and the desorbent does not contain components with strong adsorption on X-type molecular sieves and Y-type molecular sieves, such as aromatic hydrocarbons and olefins; preferably, the desorbent includes one or more of normal alkanes with a carbon number of 8-12, isoalkanes with a carbon number of 8-12 and cycloalkanes with a carbon number of 8-12, for example, it may include one or more of n-nonane, n-decane, n-dodecane, cyclooctane, n-octane and isooctane; when the desorbent contains more than two substances, there is no specific restriction on their ratio, that is, any ratio can realize the technical solution of the present disclosure.
[0086] According to one embodiment of the present disclosure, the temperatures of the first contact and the second contact are 50-200° C., and the pressures are 1.0-4.0 MPa, respectively. The above condition range can ensure that the logistics is in liquid phase at the adsorption temperature.
[0087] According to one embodiment of the present disclosure, a liquid phase simulated moving bed process is used to adsorb and separate cycloalkanes and dimethylalkanes from C5 / C6 alkanes, and the simulated moving bed comprises 8-24 adsorbent beds;
[0088] Step S1 comprises: bringing the raw material to be separated into the first contact with the adsorbent bed to obtain a raffinate containing the normal alkanes having a carbon number of 5-6, the monomethyl paraffins having a carbon number of 5-6 and a desorbent, and the adsorbent bed adsorbing the cycloalkanes having a carbon number of 5-6 and the dimethyl paraffins having a carbon number of 5-6 as the material to be desorbed;
[0089] Step S2 includes: bringing the desorbent into contact with the material to be desorbed for the second time to obtain the extract.
[0090] According to one embodiment of the present disclosure, the method further includes: separating the extract to obtain the cycloalkanes with a carbon number of 5-6, the dimethylalkanes with a carbon number of 5-6 and the desorbent; the separation method is conventional in the art, for example, it can be distillation, the separated desorbent can be recycled, and the total content of the cycloalkanes with a carbon number of 5-6 and the dimethylalkanes with a carbon number of 5-6 obtained by distillation is more than 80 weight %.
[0091] According to one embodiment of the present disclosure, the method further includes: separating the raffinate to obtain the normal alkanes with a carbon number of 5-6, the monomethyl alkanes with a carbon number of 5-6 and the desorbent, and the separated desorbent can be recycled; the separation method is conventional in the art, for example, it can be distillation, and the total content of the normal alkanes with a carbon number of 5-6 and the monomethyl alkanes with a carbon number of 5-6 obtained by distillation is more than 80 weight%.
[0092] According to one embodiment of the present disclosure, Figure 1As shown, the raw material to be separated from the raw material pipeline 1 enters the adsorption tower 100 for liquid phase simulated moving bed adsorption separation, wherein the dimethyl paraffin and cycloalkane are selectively adsorbed by the adsorbent, and the normal paraffin and monomethyl paraffin that are not adsorbed are mixed with the desorbent and flow out of the adsorption tower 100 as the raffinate liquid, and enter the raffinate liquid tower 200 through the raffinate liquid pipeline 3 for distillation separation of the desorbent, and the raffinate oil is obtained at the top of the tower, which is rich in normal paraffin and monomethyl paraffin, and is sent out of the system through the normal paraffin and monomethyl paraffin pipeline 5. The desorbent enters the adsorption tower through the desorbent pipeline 2 to desorb the dimethyl paraffin and cycloalkane adsorbed by the adsorbent, and flows out with the desorbent to obtain the extract, and the extract enters the extract tower 300 through the extract pipeline 4 for distillation separation of the desorbent, and the extract oil rich in dimethyl paraffin and cycloalkane is obtained at the top of the tower, and is sent out of the system through the cycloalkane and dimethyl paraffin pipeline 6. The desorbent is obtained at the bottom of the residual liquid extraction tower 200 and the extracted liquid extraction tower 300, and is respectively joined into the desorbent pipeline 2 through the desorbent pipeline 7 and the desorbent pipeline 8 and returned to the adsorption tower 100, so as to realize the recycling of the desorbent.
[0093] The method disclosed in the present invention can be used for both intermittent operation and continuous operation. According to one embodiment of the present invention, a liquid phase simulated moving bed process is used to adsorb and separate cycloalkanes and dimethylalkanes in C5 / C6 alkanes, and the simulated moving bed contains 8-24 adsorbent beds. In order to realize the continuous operation of the industrial separation device, the adsorption separation process is carried out in a simulated moving bed device having multiple adsorbent beds. The adsorbent is loaded in a column container in the form of a fixed bed. The adsorbent bed can be multiple adsorption columns connected in series, or it can be divided into multiple adsorbent beds by a screen or a grid inside an adsorption tower, and the liquid flow flows from top to bottom between the adsorbent beds. The several streams entering or leaving the adsorbent bed divide the adsorbent into at least three regions: an adsorption zone, a purification zone, and a desorption zone. Preferably, the adsorbent bed of the simulated moving bed is divided into four regions: an adsorption zone, a purification zone, a desorption zone, and a buffer zone for adsorption separation operation. The ratio of the number of beds of the adsorption zone, the purification zone, the desorption zone, and the buffer zone is (1.5-4.0): (1.2-4.0): (1.2-3.0): 1. Specifically, Figure 2As shown, in a liquid phase simulated moving bed device, the adsorbent bed layer between the raw material to be separated entering the simulated moving bed adsorption tower and the raffinate flow leaving the adsorption tower is the adsorption zone, the raw material flow containing normal alkanes, monomethyl alkanes, dimethyl alkanes and cycloalkanes enters the adsorbent bed layer from the upstream of the adsorption zone, the dimethyl alkanes and cycloalkanes therein are adsorbed into the micropores of the molecular sieve crystal particles of the adsorbent, and the normal alkanes and monomethyl alkanes that are not adsorbed flow out of the adsorbent bed layer from the downstream of the adsorption zone together with the desorbent to form the raffinate flow; the adsorbent bed layer between the extracted liquid flow leaving the adsorption tower and the raw material flow to be separated entering the adsorption tower is the purification zone, the logistics flowing from the upstream to the downstream of this zone flushes the normal alkanes and monomethyl alkanes outside the micropores of the adsorbent molecular sieve to the downstream, and the extracted liquid flow rich in dimethyl alkanes and cycloalkanes and containing the desorbent in the upstream of this zone leaves the adsorbent bed layer. The adsorbent bed between the desorbent flow entering the adsorption tower and the extracted liquid flow leaving the adsorption tower is the desorption zone. The desorbent enters from the upstream of this zone to displace the dimethyl paraffin and cycloparaffin in the micropores of the adsorbent molecular sieve, so that the adsorbent can be adsorbed again. There can also be a buffer zone between the desorbent flow and the residual liquid flow. The purpose of setting this zone is to prevent the normal paraffin and monomethyl paraffin in the adsorption zone from entering the desorption zone to pollute the extracted liquid. The adsorbent bed is fixed, and each adsorbent bed is connected to at least one logistics pipeline to transport several logistics entering or leaving the adsorption tower. Every step time, the positions of these logistics entering or leaving the adsorption tower adsorbent bed are moved to the next bed position in the same direction as the liquid flow direction, so that the relative movement direction of the adsorbent bed is opposite to the liquid flow direction in the adsorbent bed, achieving the effect of relative countercurrent simulation movement of liquid and solid phases. The extracted liquid flow and the residual liquid flow leaving the adsorption tower enter the fractionation tower respectively to separate the desorbent for recycling. The extracted liquid is separated from the desorbent to obtain the extracted oil, and the raffinate liquid is separated from the desorbent to obtain the raffinate oil. The step time is preferably 50-300 seconds.
[0094] According to one embodiment of the present disclosure, the method for preparing the adsorbent comprises the following steps:
[0095] (1) mixing a molecular sieve raw material, a binder and an auxiliary agent and performing a molding process to obtain a first product;
[0096] (2) heat treating the first product to obtain a second product;
[0097] (3) contacting a solution containing a metal source with the second product to perform an ion exchange reaction to obtain a third product;
[0098] (4) activating the third product;
[0099] The metal source includes a rubidium source and / or a cesium source;
[0100] The molecular sieve raw material includes NaY molecular sieve raw powder and / or NaX molecular sieve raw powder.
[0101] According to one embodiment of the present disclosure, in step (1), the binder includes one or more of a clay binder, silica sol and alumina sol; the clay binder includes one or more of kaolin, halloysite and attapulgite; the auxiliary agent includes one or more of lignin, sesbania powder, corn starch, bayberry tannin and methyl cellulose; when the types of binders or auxiliary agents are more than two, the present disclosure does not impose specific restrictions on their ratio.
[0102] According to one embodiment of the present disclosure, the silicon-to-aluminum ratio of the NaX molecular sieve raw powder is 2.0-3.0, and the silicon-to-aluminum ratio of the NaY molecular sieve raw powder is 3.0-6.0; the silicon-to-aluminum ratio refers to the molar ratio of SiO2 to Al2O3 in the molecular sieve raw powder.
[0103] According to one embodiment of the present disclosure, in step (1), on a dry basis, the weight ratio of the molecular sieve raw material to the binder is (80-95): (5-20), preferably (90-95): (5-10). When the weight ratio of the molecular sieve raw material to the binder is within the above range, the problems of high bulk density of the adsorbent due to excessively high binder content, decreased active component content, and poor adsorbent strength due to too low a binder content can be avoided.
[0104] According to one embodiment of the present disclosure, in step (1), the amount of the auxiliary agent used is 1-5% by weight, preferably 2-4% by weight, relative to the total weight of the molecular sieve raw material and the binder, calculated on a dry basis.
[0105] In the present disclosure, the molding process may be, for example, rolling ball molding, extrusion molding or tablet molding, and the molding process may be performed in a high-speed granulator, sugar coating machine, disc granulator, extruder, tablet press, etc. For example, rolling ball molding may be performed by placing the mixed powder into a rolling ball device, adding water to the material in the form of spraying while rolling, and adding the mixed powder into the material in the form of throwing, so that the fine powder agglomerates, becomes round, and forms small balls, and then throwing to obtain spherical particles; extrusion molding may be performed by placing the mixed powder into an extrusion device, first kneading by adding a certain amount of water, and then extruding to obtain strips, and drying, crushing and sieving the strips to obtain particles; tablet molding may be performed by placing the mixed powder into a tablet pressing device, pressing and molding, and then crushing and sieving to obtain particles.
[0106] According to one embodiment of the present disclosure, step (1) further includes: forming the product of the molding process into particles with a particle size of 0.30-1.00 mm, and performing a first drying process on the particles to obtain the first product; or, performing the first drying process on the product of the molding process, and then forming particles with a particle size of 0.30-1.00 mm to obtain the first product; the particles may be, for example, spherical particles, which have good fluidity, are easy to load evenly, and have good fluid distribution uniformity; the conditions of the first drying process include: a temperature of 80-200°C and a time of 1-4h. The first drying method is conventional in the art and is not specifically required; the above drying process can remove water in the macropores inside the particles.
[0107] According to one embodiment of the present disclosure, in step (2), the heat treatment method may be, for example, calcination, and the heat treatment conditions include: a temperature of 500-700°C and a time of 1-4 hours. When the binder used includes a clay binder, such as one or more of kaolin, halloysite and attapulgite, the heat treatment may convert it into a reactive aluminosilicate, enhance the strength of the particles, prevent pulverization during crystallization, and cause the additive to burn and decompose, forming a pore structure inside the separation adsorbent, thereby improving mass transfer performance.
[0108] According to one embodiment of the present disclosure, step (2) also includes: contacting the solid product obtained by the heat treatment with a solution containing an alkali source, an optional silicon source and an optional aluminum source, and subjecting the obtained mixture to optional aging treatment and crystallization treatment to obtain the second product.
[0109] According to one embodiment of the present disclosure, the method further comprises: washing the solid product obtained by crystallization treatment until the pH value of the washed liquid is 8.0-11.0, to obtain a second product.
[0110] According to one embodiment of the present disclosure, the alkali source includes sodium hydroxide and / or potassium hydroxide; the silicon source includes sodium silicate and / or silica sol; and the aluminum source includes sodium aluminate and / or aluminum sol.
[0111] According to one embodiment of the present disclosure, in the mixture, the molar ratio of sodium element calculated as Na2O to silicon element calculated as SiO2 is (0.6-6.7): 1, the molar ratio of silicon element calculated as SiO2 to aluminum element calculated as Al2O3 is (3.0-10.8): 1; the molar ratio of H2O to sodium element calculated as Na2O is (55-220): 1. The above feed ratio can make the binder easier to convert into NaX and / or NaY molecular sieves.
[0112] According to one embodiment of the present disclosure, the conditions for aging treatment include: time is 1-24h, preferably 5-12h; temperature is 30-60°C, preferably 30-50°C; the conditions for crystallization treatment include: time is 1-12h, preferably 4-10h; temperature is 80-98°C, preferably 90-95°C. The methods of aging treatment and crystallization treatment are conventional in the art and will not be elaborated here.
[0113] According to one embodiment of the present disclosure, in step (3), the cesium source and the rubidium source are both soluble compounds, the cesium source includes one or more of cesium chloride, cesium nitrate and cesium sulfate; the rubidium source includes one or more of rubidium chloride, rubidium nitrate and rubidium sulfate; in the solution, the concentration of the metal source is 0.1-2 mol / L.
[0114] In the present disclosure, the ion exchange reaction can be carried out in an exchange column, specifically comprising: loading the second product into the exchange column, exchanging with a solution containing a metal source, and the volume space velocity is 0.5-5h -1 , then rinse with deionized water until there are no anions such as chloride ions in the washing liquid, then introduce compressed air into the exchange column to dry the solid; alternatively, the ion exchange reaction can also be carried out in an exchange kettle, specifically comprising: loading the second product into the exchange kettle, exchanging with a solution containing a metal source, the volume ratio of the solution to the second solid being (3-10):1, then rinse with deionized water until there are no anions such as chloride ions in the washing liquid, then introduce compressed air to dry the solid; preferably, an exchange column is used for the ion exchange reaction.
[0115] According to one embodiment of the present disclosure, the conditions for the ion exchange reaction include: a time of 1-3 hours and a temperature of 20-99°C.
[0116] According to one embodiment of the present disclosure, the temperature of the activation treatment is 200-500°C, preferably 300-500°C; the time of the activation treatment is 1-4h; the activation treatment can be carried out in a dry air atmosphere, or in a vacuum condition, or in a nitrogen atmosphere to reduce the degree of hydrothermal damage of the molecular sieve at a higher temperature; the method and steps of the activation treatment are conventional in the art.
[0117] According to one embodiment of the present disclosure, step (3) further includes: subjecting the solid product obtained by the ion exchange reaction to a second drying treatment to obtain a third product; the conditions of the second drying treatment include: a time of 1-4 hours and a temperature of 80-200°C.
[0118] The following examples use Figure 2 The small-scale simulated moving bed apparatus shown was tested to verify the effect of the present disclosure.
[0119] The device has 12 adsorption columns connected in series, each column is 195 mm long, the inner diameter is 30 mm, and the total loading amount of the adsorbent is 1650 mL. The ends of the 12 columns connected in series are connected by a circulation pump to form a closed loop. The four inlet and outlet materials of the raw material to be separated, the desorbent, the extracted liquid and the residual liquid divide the 12 adsorption columns into four zones. The four adsorption columns between the raw material to be separated and the residual liquid are the adsorption zone, the three adsorption columns between the extracted liquid and the raw material to be separated are the purification zone, the three adsorption columns between the desorbent and the extracted liquid are the desorption zone, and the two adsorption columns between the residual liquid and the desorbent are the buffer zone.
[0120] During the operation of the small simulated moving bed, a micro pump is used to continuously inject desorbent and raw materials to be separated into the device, and the extracted liquid is continuously extracted from the device by a micro pump, and the residual liquid flows out of the device through pressure control. The flow rate of each area is adjusted by setting the flow rate of the circulating pump and the flow rate of the four inlet and outlet streams. Every other step time, the inlet and outlet positions of the four streams move an adsorption column in the same direction as the liquid flow, that is, from the position marked by the solid arrow to the position marked by the dotted arrow, so as to realize the continuous countercurrent simulation movement of the adsorbent and the fluid. The composition of the extracted liquid and the residual liquid is analyzed by gas chromatography, and the composition of the extracted oil and the residual oil is obtained by deducting the desorbent component.
[0121] The reagents used in the examples and comparative examples are all commercially available unless otherwise specified. The raw material to be separated is reformed tops oil from which benzene has been removed, and the composition is shown in Table 1.
[0122] Gas chromatography instrument model and test conditions: Agilent 7890 gas chromatograph was used to test the composition of the liquid sample, HP-5 chromatographic column, injection volume 0.3 μL, injection temperature 290°C, split ratio 45:1, column flow 3.9 mL / min, FID detection, detection temperature 290°C, H2 flow 35 mL / min, air flow 350 mL / min, N2 flow 20 mL / min, initial column temperature was 50°C, maintained for 3 min, heated to 150°C at a rate of 2°C / min, and maintained for 6 min.
[0123] Particle size testing method: Use the US standard sieve to select particles of 0.3-0.8 mm.
[0124] Testing method for water content: The sample is calcined at 600℃ for more than 2h, and the percentage of mass reduction is the water content.
[0125] The test method of silicon-aluminum ratio of molecular sieve is: X-ray fluorescence spectrometry (XRF) is used to analyze the mass fraction of Al2O3 and SiO2 in the adsorbent, which are recorded as m Al 、m Si , then the silicon-aluminum ratio = m Si / M Si / (mAl / M Al ), M Si and M Al are the molar masses of SiO2 and Al2O3 respectively.
[0126] Exchange degree test method: X-ray fluorescence spectrometry (XRF) is used to analyze the mass fractions of Na2O, Cs2O, and Rb2O in the adsorbent, which are recorded as m N 、m C and m R , then Cs + Degree of ion exchange = m C / M C / (m C / M C +m N / M N +m R / M R ), Rb + Degree of ion exchange = m R / M R / (m C / M C +m N / M N +m R / M R ), Cs + Ions and Rb + Total ion exchange degree = Cs + Ion exchange degree + Rb + The degree of ion exchange. N 、M C and M R They are the molar masses of Na2O, Cs2O and Rb2O respectively; the instrument model and test conditions of XRF are: 3013 X-ray fluorescence spectrometer (XRF) produced by Nippon Mechanics Co., Ltd. After drying at 120℃, the sample to be tested is ground into a powder of about 200 meshes, poured into a tablet pressing mold, and pressed into an ingot on a hydraulic press. The applied pressure is generally above 30MPa and maintained for 5s. The size of the pressed ingot is Φ30mm.
[0127] Example 1
[0128] Adsorbent X-1 was prepared by the following steps, and cycloalkanes and dimethylalkanes in C5 / C6 alkanes were separated by adsorption:
[0129] (1) 95 kg of NaX molecular sieve powder with a silicon-aluminum ratio of 2.2, 5 kg of kaolin and 2 kg of sesbania powder are uniformly mixed to form a mixed powder, and the mixed powder is rolled into balls in a rotary high-speed granulator. During the rolling process, deionized water is sprayed into the material and the mixed powder is sprinkled, and spherical particles with a particle size of 0.30-0.80 mm are sieved;
[0130] On a dry basis, the weight ratio of the NaX molecular sieve raw powder to the kaolin is 95:5, and the amount of the sesbania powder is 2% by weight relative to the total weight of the NaX molecular sieve raw powder and the kaolin;
[0131] The spherical particles are subjected to a first drying treatment to obtain a first product; the conditions of the first drying treatment include: a time of 8 hours and a temperature of 100° C.;
[0132] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0133] (3) mixing a mixed solution containing sodium silicate and NaOH with the second product, and subjecting the obtained mixture to an aging treatment and a crystallization treatment;
[0134] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 2.29:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 3.55:1; the molar ratio of H2O to sodium calculated as Na2O is 74.07:1;
[0135] The conditions of aging treatment included: temperature of 40°C and time of 1 h;
[0136] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0137] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0138] (5) The solid product obtained in step (4) was loaded into an exchange column and ion exchanged with a 0.2 mol / L CsCl aqueous solution under normal pressure at a temperature of 90° C. and an exchange volume space velocity of 5 h -1 , exchange time 6h. Then, the exchange column is washed with deionized water until the washing liquid is substantially free of chloride ions, and then compressed air is introduced into the exchange column to dry it, to obtain the third product;
[0139] (6) subjecting the third product to a second drying treatment and an activation treatment to obtain an adsorbent X-1;
[0140] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0141] The activation treatment was carried out in a dry air atmosphere at a temperature of 400°C for 2 h.
[0142] The water content of adsorbent X-1 was 1.5 wt%, Cs + The degree of ion exchange is 70% and the silicon-aluminum ratio is 2.2.
[0143] The adsorbent X-1 was loaded into the adsorption column. The composition of the raw material to be separated is shown in Table 1. There are 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. The desorbent is n-nonane. The temperature of the first contact and the second contact is 80°C, the pressure of the first contact and the pressure of the second contact are 1.0MPa, the feed flow rate is 2630mL / h, the desorbent flow rate is 1053mL / h, the residual liquid flow rate is 3330mL / h, the extract flow rate is 353mL / h, the purification zone flow rate is 2650mL / h, and the step time is 160s. The composition of the extract and the residual liquid was analyzed by gas chromatography, and the desorbent n-nonane was deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 1. According to Table 1, dimethyl paraffins and cycloalkanes account for 95.0% by weight in the extracted oil, and normal paraffins and monomethyl paraffins account for 98.2% by weight in the residual oil.
[0144] Example 2
[0145] Adsorbent X-2 was prepared by the following steps and used for the adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes:
[0146] (1) 95 kg of NaX molecular sieve powder with a silicon-aluminum ratio of 2.5, 5 kg of halloysite and 2 kg of corn starch are uniformly mixed to form a mixed powder, and the mixed powder is rolled into balls in a rotary high-speed granulator. During the rolling process, deionized water is sprayed into the material and the mixed powder is sprinkled, and spherical particles with a particle size of 0.30-0.80 mm are screened;
[0147] On a dry basis, the weight ratio of the NaX molecular sieve raw powder to the halloysite is 95:5, and the amount of corn starch used is 2% by weight relative to the total weight of the NaX molecular sieve raw powder and the halloysite;
[0148] The spherical particles are subjected to a first drying treatment to obtain a first product; the conditions of the first drying treatment include: a time of 8 hours and a temperature of 100° C.;
[0149] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0150] (3) mixing a mixed solution containing sodium silicate and NaOH with the second product, and subjecting the obtained mixture to an aging treatment and a crystallization treatment;
[0151] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 1.70:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 3.19:1; the molar ratio of H2O to sodium calculated as Na2O is 111.11:1;
[0152] The conditions of aging treatment included: temperature of 40°C and time of 1 h;
[0153] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0154] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0155] (5) The solid product obtained in step (4) was loaded into an exchange column and ion exchanged with a 0.2 mol / L RbCl aqueous solution under normal pressure at a temperature of 90° C. and an exchange volume space velocity of 5 h -1 , exchange time 6h. Then, the exchange column is washed with deionized water until the washing liquid is substantially free of chloride ions, and then compressed air is introduced into the exchange column to dry it, to obtain the third product;
[0156] (6) subjecting the third product to a second drying treatment and an activation treatment to obtain an adsorbent X-2;
[0157] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0158] The activation treatment was carried out in a dry air atmosphere at a temperature of 500°C for 2 h.
[0159] The water content of adsorbent X-2 was 0.5 wt%, Rb + The degree of ion exchange is 69% and the silicon-aluminum ratio is 2.5.
[0160] The adsorbent X-2 is loaded in the adsorption column. The composition of the raw material to be separated is shown in Table 1. There are 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. The desorbent is n-decane. The temperature of the first contact and the second contact is 100°C, the pressure of the first contact and the pressure of the second contact are 1.5MPa, the feed flow rate is 2630mL / h, the desorbent flow rate is 1053mL / h, the residual liquid flow rate is 3330mL / h, the extracted liquid flow rate is 353mL / h, the purification zone flow rate is 2670mL / h, and the step time is 160s. The composition of the extracted liquid and the residual liquid is analyzed by gas chromatography, and the desorbent n-nonane is deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 1. According to Table 1, dimethyl paraffins and cycloalkanes account for 99.0% by weight in the extracted oil, and normal paraffins and monomethyl paraffins account for 97.8% by weight in the residual oil.
[0161] Example 3
[0162] Adsorbent X-3 was prepared by the following steps and used for the adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes:
[0163] (1) 95 kg of NaY molecular sieve powder with a silicon-aluminum ratio of 6.0, 5 kg of silica sol and 2 kg of corn starch are uniformly mixed to form a mixed powder, and the mixed powder is rolled into balls in a rotary high-speed granulator. During the rolling process, deionized water is sprayed into the material and the mixed powder is sprinkled, and spherical particles with a particle size of 0.30-0.80 mm are sieved;
[0164] On a dry basis, the weight ratio of the NaY molecular sieve raw powder to the silica sol is 95:5, and the amount of corn starch used is 2% by weight relative to the total weight of the NaY molecular sieve raw powder and the silica sol;
[0165] The spherical particles are subjected to a first drying treatment to obtain a first product; the conditions of the first drying treatment include: a time of 8 hours and a temperature of 100° C.;
[0166] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0167] (3) mixing a mixed solution containing sodium metaaluminate, sodium silicate and NaOH with the second product, and subjecting the obtained mixture to a crystallization treatment;
[0168] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 1.52:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 5.37:1; the molar ratio of H2O to sodium calculated as Na2O is 74.07:1;
[0169] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0170] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0171] (5) The solid product obtained in step (4) was loaded into an exchange column and ion exchanged with 0.2 mol / L RbCl and 0.2 mol / L CsCl aqueous solution under normal pressure at a temperature of 90° C. and a volume space velocity of 5 h -1 , exchange time 4h. Then, the exchange column is washed with deionized water until the washing liquid is substantially free of chloride ions, and then compressed air is introduced into the exchange column to dry it, thereby obtaining the third product;
[0172] (6) subjecting the third product to a second drying treatment and an activation treatment to obtain an adsorbent X-3;
[0173] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0174] The activation treatment was carried out in a dry air atmosphere at a temperature of 230°C for 2 h.
[0175] The water content of adsorbent X-3 was 5.0 wt%, Cs + Ions and Rb + The total ion exchange degree is 68% and the silicon-aluminum ratio is 6.0.
[0176] The adsorbent X-3 is loaded in the adsorption column. The composition of the raw material to be separated is shown in Table 1, with 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. The desorbent is n-dodecane. The temperature of the first contact and the second contact is 120°C, the pressure of the first contact and the pressure of the second contact are 1.5MPa, the feed flow rate is 2630mL / h, the desorbent flow rate is 1053mL / h, the residual liquid flow rate is 3330mL / h, the extracted liquid flow rate is 353mL / h, the purification zone flow rate is 2630mL / h, and the step time is 160s. The composition of the extracted liquid and the residual liquid is analyzed by gas chromatography, and the desorbent n-dodecane is deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 1. According to Table 1, dimethyl paraffins and cycloalkanes account for 94.0% by weight in the extracted oil, and normal paraffins and monomethyl paraffins account for 97.7% by weight in the residual oil.
[0177] Example 4
[0178] Adsorbent X-4 was prepared by the following steps and used for the adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes:
[0179] (1) 95 kg of NaX molecular sieve powder with a silicon-aluminum ratio of 2.7, 5 kg of silica sol and 2 kg of corn starch are uniformly mixed to form a mixed powder, 50 kg of deionized water is added, the mixture is put into a kneader and kneaded for 30 min, and then extruded into strips in an extruder, and a first drying treatment is performed at 100° C. for 4 h. Particles with a particle size of 0.30-0.80 mm are sieved to obtain the first product;
[0180] On a dry basis, the weight ratio of the NaX molecular sieve raw powder to the silica sol is 95:5, and the amount of corn starch used is 2% by weight relative to the total weight of the NaX molecular sieve raw powder and the silica sol;
[0181] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0182] (3) mixing a mixed solution containing sodium metaaluminate and NaOH with the second product, and subjecting the obtained mixture to an aging treatment and a crystallization treatment;
[0183] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 1.93:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 3.37:1; the molar ratio of H2O to sodium calculated as Na2O is 92.59;
[0184] The conditions of aging treatment included: temperature of 30°C and time of 12 h;
[0185] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0186] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0187] (5) The solid product obtained in step (4) is placed in an exchange kettle, and ion exchange is performed with a 0.2 mol / L CsCl aqueous solution under normal pressure, the exchange temperature is 90° C., the volume ratio of the exchange solution to the solid product is 3:1, and the exchange time is 4 hours. The solid is then washed with deionized water until the washing liquid is substantially free of chloride ions, and then compressed air is introduced to dry the solid to obtain a third product;
[0188] (6) subjecting the third product to a second drying treatment and an activation treatment to obtain an adsorbent X-4;
[0189] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0190] The activation treatment was carried out in a dry air atmosphere at a temperature of 500°C for 2 h.
[0191] The water content of adsorbent X-4 was 0.4 wt%, Cs + The degree of ion exchange is 20% and the silicon-aluminum ratio is 2.7.
[0192] The adsorbent X-4 was loaded into the adsorption column. The composition of the raw material to be separated is shown in Table 2. There are 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. The desorbent is n-nonane. The temperature of the first contact and the second contact is 200°C, the pressure of the first contact and the pressure of the second contact are 4.0MPa, the feed flow rate is 2630mL / h, the desorbent flow rate is 1053mL / h, the residual liquid flow rate is 3330mL / h, the extracted liquid flow rate is 353mL / h, the purification zone flow rate is 2690mL / h, and the step time is 160s. The composition of the extracted liquid and the residual liquid was analyzed by gas chromatography, and the desorbent n-nonane was deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 2. According to Table 2, dimethyl paraffins and cycloalkanes account for 90.0% by weight in the extracted oil, and normal paraffins and monomethyl paraffins account for 96.9% by weight in the residual oil.
[0193] Example 5
[0194] Adsorbent X-5 was prepared by the following steps and used for the adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes:
[0195] (1) 45 kg of NaX molecular sieve powder with a silicon-aluminum ratio of 2.7, 50 kg of NaY molecular sieve powder with a silicon-aluminum ratio of 5.0, 2 kg (on a dry basis) of attapulgite, 3 kg (on a dry basis) of halloysite, 1 kg of bayberry tannin extract and 1 kg of corn starch are mixed evenly to form a mixed powder, which is put into a tablet press to form tablets, subjected to a first drying treatment at 100° C. for 4 h, and the flakes are crushed to obtain crushed particles of 0.30-0.80 mm, which are the first product;
[0196] On a dry basis, the weight ratio of the molecular sieve raw powder to the binder is 95:5, and the amount of the additive is 2% by weight relative to the total weight of the molecular sieve raw powder and the binder;
[0197] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0198] (3) mixing a mixed solution containing sodium metaaluminate, sodium silicate and NaOH with the second product, and subjecting the obtained mixture to a crystallization treatment;
[0199] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 1.83:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 4.46:1; the molar ratio of H2O to sodium calculated as Na2O is 74.07:1;
[0200] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0201] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0202] (5) The solid product obtained in step (4) is placed in an exchange kettle, and ion exchange is performed with a 0.4 mol / L CsCl aqueous solution under normal pressure, the exchange temperature is 90° C., the volume ratio of the exchange solution to the solid product is 4:1, and the exchange time is 4 h. The solid is then washed with deionized water until the washing liquid is substantially free of chloride ions, and then compressed air is introduced to dry the solid to obtain a third product;
[0203] (6) subjecting the third product to a second drying treatment and an activation treatment to obtain an adsorbent X-5;
[0204] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0205] The activation treatment was carried out in a dry air atmosphere at a temperature of 500°C for 2 h.
[0206] The water content of adsorbent X-5 was 0.4 wt%, Cs + The degree of ion exchange is 50% and the silicon-aluminum ratio is 3.7.
[0207] The adsorbent X-5 was loaded into the adsorption column. The composition of the raw material to be separated is shown in Table 2. There are 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. A mixture of 70 wt% n-nonane and 30 wt% isooctane was used as the desorbent. The temperature of the first contact and the second contact was 120°C, the pressure of the first contact and the pressure of the second contact were 4.0 MPa, the feed flow rate was 2630 mL / h, the desorbent flow rate was 1053 mL / h, the residual liquid flow rate was 3360 mL / h, the extract flow rate was 323 mL / h, the purification zone flow rate was 2600 mL / h, and the step time was 160 s. The composition of the extract and the residual liquid was analyzed by gas chromatography, and the desorbent n-nonane and isooctane were deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 2. According to Table 2, dimethyl paraffins and cycloparaffins account for 93.0% by weight of the extracted oil, and normal paraffins and monomethyl paraffins account for 96.9% by weight of the raffinate oil.
[0208] Example 6
[0209] Adsorbent X-6 was prepared by the following steps and used for the adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes:
[0210] (1) 95 kg of NaX molecular sieve powder with a silicon-aluminum ratio of 2.4, 5 kg of kaolin and 2 kg of sesbania powder are uniformly mixed to form a mixed powder, and the mixed powder is rolled into balls in a rotary high-speed granulator. During the rolling process, deionized water is sprayed into the material and the mixed powder is sprinkled, and spherical particles with a particle size of 0.30-0.80 mm are sieved;
[0211] On a dry basis, the weight ratio of the NaX molecular sieve raw powder to the kaolin is 95:5, and the amount of the sesbania powder is 2% by weight relative to the total weight of the NaX molecular sieve raw powder and the kaolin;
[0212] The spherical particles are subjected to a first drying treatment to obtain a first product; the conditions of the first drying treatment include: a time of 8 hours and a temperature of 100° C.;
[0213] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0214] (3) mixing a mixed solution containing sodium silicate and NaOH with the second product, and subjecting the obtained mixture to an aging treatment and a crystallization treatment;
[0215] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 2.29:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 3.55:1; the molar ratio of H2O to sodium calculated as Na2O is 74.07:1;
[0216] The conditions of aging treatment included: temperature of 40°C and time of 1 h;
[0217] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0218] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0219] (5) The solid product obtained in step (4) is placed in an exchange kettle, and ion exchange is performed with a 0.2 mol / L RbCl aqueous solution under normal pressure, the exchange temperature is 90°C, the volume ratio of the exchange liquid to the solid product is 3:1, and the exchange time is 4 hours. The solid is then washed with deionized water until the washing liquid is substantially free of chloride ions, and then compressed air is introduced to dry the solid to obtain a third product;
[0220] (6) subjecting the third product to a second drying treatment and an activation treatment to obtain an adsorbent X-6;
[0221] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0222] The activation treatment was carried out in a dry air atmosphere at a temperature of 400°C for 2 h.
[0223] The water content of adsorbent X-6 was 1.5 wt%, Rb + The degree of ion exchange is 20% and the silicon-aluminum ratio is 2.4.
[0224] The adsorbent X-6 was loaded into the adsorption column. The composition of the raw material to be separated is shown in Table 2. There were 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. A mixture of 50% by weight of n-octane, 30% by weight of isooctane, and 20% by weight of cyclooctane was used as the desorbent. The temperature of the first contact and the second contact was 80°C, the pressure of the first contact and the pressure of the second contact were 1.0 MPa, the feed flow rate was 2630 mL / h, the desorbent flow rate was 1053 mL / h, the residual liquid flow rate was 3380 mL / h, the extracted liquid flow rate was 303 mL / h, the purification zone flow rate was 2600 mL / h, and the step time was 160 s. The composition of the extracted liquid and the residual liquid was analyzed by gas chromatography. The desorbent n-octane, isooctane and cyclooctane were deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 2. According to Table 2, dimethyl paraffins and cycloparaffins account for 90.0% by weight of the extracted oil, and normal paraffins and monomethyl paraffins account for 96.4% by weight of the raffinate oil.
[0225] Example 7
[0226] Adsorbent X-7 was prepared by the following steps and used for the adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes:
[0227] (1) 95 kg of NaX molecular sieve powder with a silicon-aluminum ratio of 2.2, 5 kg of kaolin and 2 kg of sesbania powder are uniformly mixed to form a mixed powder, and the mixed powder is rolled into balls in a rotary high-speed granulator. During the rolling process, deionized water is sprayed into the material and the mixed powder is sprinkled, and spherical particles with a particle size of 0.30-0.80 mm are sieved;
[0228] On a dry basis, the weight ratio of the NaX molecular sieve raw powder to the kaolin is 95:5, and the amount of the sesbania powder is 2% by weight relative to the total weight of the NaX molecular sieve raw powder and the kaolin;
[0229] The spherical particles are subjected to a first drying treatment to obtain a first product; the conditions of the first drying treatment include: a time of 8 hours and a temperature of 100° C.;
[0230] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0231] (3) mixing a mixed solution containing sodium silicate and NaOH with the second product, and subjecting the obtained mixture to an aging treatment and a crystallization treatment;
[0232] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 2.29:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 3.55:1; the molar ratio of H2O to sodium calculated as Na2O is 74.07:1;
[0233] The conditions of aging treatment included: temperature of 40°C and time of 1 h;
[0234] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0235] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0236] (5) The solid product obtained in step (4) is placed in an exchange kettle, and ion exchange is performed with a 0.1 mol / L CsCl aqueous solution under normal pressure, the exchange temperature is 90° C., the volume ratio of the exchange liquid to the solid product is 3:1, and the exchange time is 6 hours. The exchange column is then washed with deionized water until the washing liquid is substantially free of chloride ions, and then compressed air is introduced into the exchange column to dry it, to obtain a third product;
[0237] (6) subjecting the third product to a second drying treatment and an activation treatment to obtain an adsorbent X-7;
[0238] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0239] The activation treatment was carried out in a dry air atmosphere at a temperature of 400°C for 2 h.
[0240] The water content of adsorbent X-7 was 1.5 wt%, Cs + The degree of ion exchange is 14% and the silicon-aluminum ratio is 2.2.
[0241] The adsorbent X-7 was loaded into the adsorption column. The composition of the raw material to be separated is shown in Table 1, 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. The desorbent is n-nonane. The temperature of the first contact and the second contact was 80°C, the pressure of the first contact and the pressure of the second contact were 1.0MPa, the feed flow rate was 2630mL / h, the desorbent flow rate was 1053mL / h, the residual liquid flow rate was 3330mL / h, the extracted liquid flow rate was 353mL / h, the purification zone flow rate was 2650mL / h, and the step time was 160s. The composition of the extracted liquid and the residual liquid was analyzed by gas chromatography, and the desorbent n-nonane was deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 2. According to Table 2, dimethyl paraffins and cycloalkanes accounted for 70.0% by weight in the extracted oil, and normal paraffins and monomethyl paraffins accounted for 93.7% by weight in the residual oil.
[0242] Comparative Example 1
[0243] Adsorbent Y-1 was prepared by the following steps and used for the adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes:
[0244] (1) 95 kg of NaX molecular sieve powder with a silicon-aluminum ratio of 2.5, 5 kg of halloysite and 2 kg of corn starch are uniformly mixed to form a mixed powder, and the mixed powder is rolled into balls in a rotary high-speed granulator. During the rolling process, deionized water is sprayed into the material and the mixed powder is sprinkled, and spherical particles with a particle size of 0.30-0.80 mm are screened;
[0245] On a dry basis, the weight ratio of the NaX molecular sieve raw powder to the halloysite is 95:5, and the amount of corn starch used is 2% by weight relative to the total weight of the NaX molecular sieve raw powder and the halloysite;
[0246] The spherical particles are subjected to a first drying treatment to obtain a first product; the conditions of the first drying treatment include: a time of 8 hours and a temperature of 100° C.;
[0247] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0248] (3) mixing a mixed solution containing sodium silicate and NaOH with the second product, and subjecting the obtained mixture to an aging treatment and a crystallization treatment;
[0249] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 1.70:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 3.19:1; the molar ratio of H2O to sodium calculated as Na2O is 111.11:1;
[0250] The conditions of aging treatment included: temperature of 40°C and time of 1 h;
[0251] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0252] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0253] (5) subjecting the solid product obtained in step (4) to a second drying treatment and an activation treatment to obtain an adsorbent Y-1;
[0254] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0255] The activation treatment was carried out in a dry air atmosphere at a temperature of 500°C for 2 h.
[0256] The water content of adsorbent Y-1 was 0.5 wt%.
[0257] The adsorbent Y-1 was loaded into the adsorption column. The composition of the raw material to be separated is shown in Table 3. There are 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. The desorbent is n-decane. The temperature of the first contact and the second contact is 100°C, the pressure of the first contact and the pressure of the second contact are 1.5MPa, the feed flow rate is 2630mL / h, the desorbent flow rate is 1053mL / h, the residual liquid flow rate is 3330mL / h, the extracted liquid flow rate is 353mL / h, the purification zone flow rate is 2670mL / h, and the step time is 160s. The composition of the extracted liquid and the residual liquid was analyzed by gas chromatography, and the desorbent n-nonane was deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 3. According to Table 3, dimethyl paraffins and cycloalkanes account for 30.0% by weight in the extracted oil, and normal paraffins and monomethyl paraffins account for 90.5% by weight in the residual oil.
[0258] Comparative Example 2
[0259] Adsorbent Y-2 was prepared by the following steps and used for the adsorption separation of cycloalkanes and dimethylalkanes in C5 / C6 alkanes:
[0260] (1) 95 kg of NaY molecular sieve powder with a silicon-aluminum ratio of 6.0, 5 kg of silica sol and 2 kg of corn starch are uniformly mixed to form a mixed powder, and the mixed powder is rolled into balls in a rotary high-speed granulator. During the rolling process, deionized water is sprayed into the material and the mixed powder is sprinkled, and spherical particles with a particle size of 0.30-0.80 mm are sieved;
[0261] On a dry basis, the weight ratio of the NaY molecular sieve raw powder to the silica sol is 95:5, and the amount of corn starch used is 2% by weight relative to the total weight of the NaY molecular sieve raw powder and the silica sol;
[0262] The spherical particles are subjected to a first drying treatment to obtain a first product; the conditions of the first drying treatment include: a time of 8 hours and a temperature of 100° C.;
[0263] (2) calcining the first product to obtain a second product; the calcination temperature is 540° C. and the time is 4 h;
[0264] (3) mixing a mixed solution containing sodium metaaluminate, sodium silicate and NaOH with the second product, and subjecting the obtained mixture to an aging treatment and a crystallization treatment;
[0265] In the mixture, the molar ratio of sodium calculated as Na2O to silicon calculated as SiO2 is 1.52:1, the molar ratio of silicon calculated as SiO2 to aluminum calculated as Al2O3 is 5.37:1; the molar ratio of H2O to sodium calculated as Na2O is 74.07:1;
[0266] The conditions of the crystallization treatment include: temperature of 91°C and time of 4 h;
[0267] (4) washing the solid product obtained in step (3) with deionized water until the pH value of the washed solution is 10.0;
[0268] (5) subjecting the solid product obtained in step (4) to a second drying treatment and an activation treatment to obtain an adsorbent Y-2;
[0269] The conditions of the second drying treatment include: temperature of 100°C and time of 4h;
[0270] The activation treatment was carried out in a dry air atmosphere at a temperature of 230°C for 2 h.
[0271] The water content of adsorbent Y-2 was 5.0 wt%.
[0272] The adsorbent Y-2 was loaded into the adsorption column. The composition of the raw material to be separated is shown in Table 3. There are 4 columns in the adsorption zone, 3 columns in the purification zone, 3 columns in the desorption zone, and 2 columns in the buffer zone. The desorbent is n-dodecane. The temperature of the first contact and the second contact is 120°C, the pressure of the first contact and the pressure of the second contact are 1.5MPa, the feed flow rate is 2630mL / h, the desorbent flow rate is 1053mL / h, the residual liquid flow rate is 3330mL / h, the extracted liquid flow rate is 353mL / h, the purification zone flow rate is 2630mL / h, and the step time is 160s. The composition of the extracted liquid and the residual liquid was analyzed by gas chromatography, and the desorbent n-dodecane was deducted to obtain the composition of the extracted oil and the residual oil, respectively, as shown in Table 3. According to Table 3, dimethyl paraffins and cycloalkanes account for 32.0% by weight in the extracted oil, and normal paraffins and monomethyl paraffins account for 90.2% by weight in the residual oil.
[0273] Table 1
[0274]
[0275] Table 2
[0276]
[0277] Table 3
[0278]
[0279]
[0280] According to the above data, it can be seen that the method disclosed in the present invention is capable of separating C5 / C6 alkanes to obtain high-purity dimethyl paraffins and cycloparaffins, as well as high-purity normal paraffins and monomethyl paraffins.
[0281] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0282] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0283] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for separating cycloalkanes and dimethylalkanes from C5 / C6 alkanes by adsorptive separation, characterized in that: The method comprises the following steps: S1, bringing the raw material to be separated into first contact with the adsorbent to obtain a material to be desorbed comprising cycloalkanes having a carbon number of 5-6, dimethylalkanes having a carbon number of 5-6 and the adsorbent, and a raffinate comprising normal alkanes having a carbon number of 5-6, monomethylalkanes having a carbon number of 5-6 and the desorbent; S2, bringing the desorbent into second contact with the material to be desorbed to obtain an extract containing cycloalkanes having a carbon number of 5-6, dimethylalkanes having a carbon number of 5-6 and the desorbent; The raw materials to be separated include normal alkanes with carbon atoms of 5-6, cycloalkanes with carbon atoms of 5-6, dimethylalkanes with carbon atoms of 5-6, and monomethylalkanes with carbon atoms of 5-6; The adsorbent includes a FAU type molecular sieve, and the metal cations in the FAU type molecular sieve include Cs + ions and / or Rb + ion.
2. The method according to claim 1, wherein: In the FAU type molecular sieve, the Cs + ions and the Rb + The total degree of ion exchange is 20-70%; Optionally, the silicon to aluminum ratio of the FAU type molecular sieve is 2.0-6.0; Optionally, the FAU type molecular sieve includes an X type molecular sieve and / or a Y type molecular sieve.
3. The method according to claim 1, wherein: The water content of the adsorbent is less than 5% by weight.
4. The method according to claim 1, wherein: The boiling point difference between the desorbent and the raw material to be separated is more than 10°C; Preferably, the desorbent includes one or more of normal alkanes with carbon atoms of 8-12, isoalkanes with carbon atoms of 8-12, and cycloalkanes with carbon atoms of 8-12.
5. The method according to claim 1, wherein: The temperature of the first contact and the second contact are 50-200° C., and the pressure are 1.0-4.0 MPa, respectively.
6. The method according to claim 1, wherein: The liquid phase simulated moving bed process is used to separate cycloalkanes and dimethylalkanes from C5 / C6 alkanes by adsorption, and the simulated moving bed contains 8-24 adsorbent beds; Step S1 comprises: bringing the raw material to be separated into the first contact with the adsorbent bed to obtain a raffinate containing the normal alkanes having a carbon number of 5-6, the monomethyl paraffins having a carbon number of 5-6 and a desorbent, and the adsorbent bed adsorbing the cycloalkanes having a carbon number of 5-6 and the dimethyl paraffins having a carbon number of 5-6 as the material to be desorbed; Step S2 includes: bringing the desorbent into contact with the material to be desorbed for the second time to obtain the extract.
7. The method according to claim 1 or 6, wherein: The method further comprises: Separating the extracted liquid to obtain the cycloalkanes with a carbon number of 5 to 6, the dimethylalkanes with a carbon number of 5 to 6 and the desorbent; The raffinate is separated to obtain the normal alkanes with a carbon number of 5-6, the monomethyl alkanes with a carbon number of 5-6 and the desorbent.
8. The method according to claim 1, wherein: The method for preparing the adsorbent comprises the following steps: (1) mixing a molecular sieve raw material, a binder and an auxiliary agent and performing a molding process to obtain a first product; (2) heat treating the first product to obtain a second product; (3) contacting a solution containing a metal source with the second product to perform an ion exchange reaction to obtain a third product; (4) activating the third product; The metal source includes a rubidium source and / or a cesium source; The molecular sieve raw material includes NaY molecular sieve raw powder and / or NaX molecular sieve raw powder.
9. The method according to claim 8, wherein: In step (1), the binder includes one or more of a clay binder, silica sol and alumina sol; The clay binder includes one or more of kaolin, halloysite and attapulgite; The auxiliary agent includes one or more of lignin, sesbania powder, corn starch, bayberry tannin and methyl cellulose; Optionally, the silicon-aluminum ratio of the NaX molecular sieve raw powder is 2.0-3.0, and the silicon-aluminum ratio of the NaY molecular sieve raw powder is 3.0-6.
0.
10. The method according to claim 8, wherein: In step (1), the weight ratio of the molecular sieve raw material to the binder is (80-95): (5-20) on a dry basis; On a dry basis, the amount of the auxiliary agent used is 1-5% by weight relative to the total weight of the molecular sieve raw material and the binder.
11. The method according to claim 8, wherein: Step (1) further includes: forming the product of the molding process into particles with a particle size of 0.30-1.00 mm, and performing a first drying process on the particles to obtain the first product; Alternatively, the product of the molding process is subjected to the first drying process, and then formed into particles with a particle size of 0.30-1.00 mm to obtain the first product; The conditions of the first drying treatment include: temperature of 80-200° C. and time of 1-4 hours.
12. The method according to claim 8, wherein: In step (2), the heat treatment conditions include: temperature of 500-700°C and time of 1-4h; Optionally, step (2) further comprises: contacting the solid product obtained by the heat treatment with a solution comprising an alkali source, an optional silicon source and an optional aluminum source, and subjecting the obtained mixture to optional aging treatment and crystallization treatment to obtain the second product; In the mixture, the molar ratio of sodium element calculated as Na2O to silicon element calculated as SiO2 is (0.6-6.7):1, the molar ratio of silicon element calculated as SiO2 to aluminum element calculated as Al2O3 is (3.0-10.8):1; the molar ratio of H2O to sodium element calculated as Na2O is (55-220):1; Optionally, the aging treatment conditions include: time of 1-24h, temperature of 30-60°C; Optionally, the conditions of the crystallization treatment include: time of 1-12h, temperature of 80-98°C; The alkali source includes sodium hydroxide and / or potassium hydroxide; The silicon source includes sodium silicate and / or silica sol; The aluminum source includes sodium metaaluminate and / or aluminum sol.
13. The method according to claim 8, wherein: In step (3), the cesium source includes one or more of cesium chloride, cesium nitrate and cesium sulfate; The rubidium source includes one or more of rubidium chloride, rubidium nitrate and rubidium sulfate; In the solution, the concentration of the metal source is 0.1-2.0 mol / L; The conditions of the ion exchange reaction include: time of 1-3h, temperature of 20-99°C; Optionally, step (3) further comprises: subjecting the solid product obtained by the ion exchange reaction to a second drying treatment to obtain the third product; The conditions of the second drying treatment include: time of 1-4 hours and temperature of 80-200°C.
14. The method according to claim 8, wherein: In step (4), the temperature of the activation treatment is 200-500° C., and the time of the activation treatment is 1-4 hours.
Citation Information
Patent Citations
Adsorption and separation method of C5 and C6 isomerization product
CN102452885B